Aqueous Extract of Black Maca (Lepidium meyenii) on Memory Impairment Induced by Ovariectomy in Mice. (14th February 2011) - Rubio, Julio; Qiong, Wang; Liu, Xinmin; Jiang, Zhen; Dang, Haixia; Chen, Shi-Lin; Gonzales, Gustavo F.
Abstract : The present study aims to test two different doses of aqueous extract of black maca on learning and memory in ovariectomized (OVX) mice and their relation with malonalehyde (MDA), acetylcholinesterase (Ache) and monoamine oxidase (MAO) brain levels. Female mice were divided into five groups: (i) naive (control), (ii) sham, (iii) OVX mice and OVX mice treated with (iv) 0.50 g kg −1 and (v) 2.00 g kg −1 black maca. Mice were orally treated with distilled water or black maca during 35 days starting 7 days after surgery. Memory and learning were assessed using the water Morris maze (from day 23–27) and the step-down avoidance test (days 34 and 35). At the end of each treatment, mice were sacrificed by decapitation and brains were dissected out for MDA, Ache and MAO determinations. Black maca (0.5 and 2.0 g/kg) increased step-down latency when compared to OVX control mice. Black maca decreased MDA and Ache levels in OVX mice; whereas, no differences were observed in MAO levels. Finally, black maca improved experimental memory impairment induced by ovariectomy, due in part, by its antioxidant and Ache inhibitory activities.